Laminar burning velocities, CO, and NOx emissions of premixed polyoxymethylene dimethyl ether flames. (1st June 2021) - Eckart, Sven; Cai, Liming; Fritsche, Chris; vom Lehn, Florian; Pitsch, Heinz; Krause, Hartmut
Graphical abstract: Abstract: Polyoxymethylene dimethyl ethers (OMEn ) with the chemical structure of CH 3 O ( CH 2 O ) n CH 3 are a promising synthetic e-fuel class that can be produced from renewable electricity and improves the emission characteristics of internal combustion engines. However, knowledge of their fundamental combustion properties, such as the laminar burning velocity, is limited in the literature, preventing the full assessment of their application potential in combustion devices. Thus, a heat flux burner is applied in this study to measure the laminar burning velocities of OME1 and OME2 over a wide range of equivalence ratios of 0.6–1.9 and at initial temperatures of 383–401 K under atmospheric pressure for the first time. The obtained data are compared with computed results using a recently developed reaction mechanism for OME1–4 . Good agreement is observed. The experimental results are also discussed in the context of a comparison to literature data of dimethyl ether and OME3, demonstrating the minor impact of chain length of (OMEn ) on their burning velocities, which is further analyzed in terms of sensitivity analysis on reaction kinetics. Furthermore, the exhaust gas composition of NO x and CO is determined experimentally for flames of OME1 and OME2 using a probe method and compared to the numerical results, observing mostly good agreement, where the remaining differences could be explained on the basis of combined experimental and model uncertainties. This provides unique knowledge on the emission performance of the combustion of (OMEn ).